PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN MENGINAP (STUDI PADA PELANGGAN STAR HOTEL SEMARANG) - Putranti, Clara Sapphira; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
The service industry sector, such as hospitality, is a fast growing business in Indonesia.These business opportunities lead to competition between hospitality services in providing the best services to attract and retain consumers. One of the hospitality services with a good rating is Star Hotel Semarang. As a company engaged in the service sector, it must prioritize good service to its customers at prices according to what has been provided by Star Hotel Semarang in order to create a purchasing decision.This study aims to determine the effect of service quality and price on decision to stay (studies on consumers Star Hotel Semarang). This type of research is explanatory research. The sampling techniques used are incidental sampling and purposive sampling. The number of samples taken is 100 respondents, who are consumers of Star Hotel Semarang. The research that is used to determine the effect of service quality and price on decision to stay will present statistics with the help of IBM SPSS version 21.0.